2018
DOI: 10.4084/mjhid.2018.006
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Early Stages Hodgkin Lymphoma During Pregnancy

Abstract: BackgroundTo assess maternal and fetal outcome of women and newborns who received chemotherapy during pregnancy to treat Hodgkin lymphoma (HL)in early stages (IA, IIA), we performed a retrospective analysis of a cohort of 44 pregnant women with HL and early stages, diagnosed and treated between 1988 to 2013, at a tertiary reference cancer center.MethodsWe analyzed data on HL characteristics and treatment, with a particular attention to maternal and fetal complications; in children, we performed a longer follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Another series on 44 pregnant patients with chemotherapy for early stage HL during pregnancy reported 22% preterm delivery, but no other obstetric complications. 10 A breast cancer series also found a higher obstetric complication rate in patients receiving antenatal cancer treatment compared to patients without antenatal treatment, but similar to this HL series, no specific complication was significantly more prevalent in the exposed group. 21 In one cohort study caesarean section or induction of labour were considered as complications and were more common in the non-exposed group.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Another series on 44 pregnant patients with chemotherapy for early stage HL during pregnancy reported 22% preterm delivery, but no other obstetric complications. 10 A breast cancer series also found a higher obstetric complication rate in patients receiving antenatal cancer treatment compared to patients without antenatal treatment, but similar to this HL series, no specific complication was significantly more prevalent in the exposed group. 21 In one cohort study caesarean section or induction of labour were considered as complications and were more common in the non-exposed group.…”
Section: Discussionsupporting
confidence: 66%
“…We did not find an increased rate of neonatal morbidity in this series, consistent with prior data. 8,10,13 The major congenital malformation rate was comparable to that of the general population, with a background risk of 2•8 to 6•9% for major malformations and 6•5 to 35•8% for minor abnormalities. 25,26 In the literature of the non-pregnant population 5 year PFS ranges between 86•4 and 94•2% and 5 year OS between 96•0 and 98•8% for early stage HL.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…protocol remains the current treatment for HL in pregnancy in North America and Europe [13,14]. Small case series and retrospective studies in pregnancies treated for HL reported that doxorubicin was safe for the fetal heart when administered during the second and third trimester [9,12,[15][16][17]. But they reported that doxorubicin in pregnancy could reduce the thickness of the left ventricular wall without causing heart defects or functional disorders [15].…”
mentioning
confidence: 99%